JUDICIAL DECISION AND RETHINKING THE CONSTITUTIONAL PRINCIPLES CONCERNING TREATY MAKING POWER AND PROCESS OF THAILAND - Umpai, Kiarttiphorn (Faculty of Law, Universitas Brawijaya, 2017)
This paper aims to examine the treaty making power and process in recent constitutional provisions reforms in Thailand. It aims to analyze whether the constitutional provision has affected the treaty-making crisis. This study relied on the theory of the sovereignty of state exercised by the executive branch in compliance with the treaty making power concept, the separation of powers, and the checks and balances doctrine. The findings revealed that Thailand’s constitutional amendment related to treaty making processes, proposing a negotiation framework approved by the legislative branch or public participation during a prior negotiation period, is not in compliance with the treaty making concept and state practices of foreign countries. However, Thailand has already reformed the constitutional provision. The implications are that there must be an amendment to the Constitution defining the processes and characteristics of treaties that shall be approved by the legislative branch